2017
DOI: 10.1063/1.5000792
|View full text |Cite
|
Sign up to set email alerts
|

Structural stabilities and electronic properties of Mg28-nAln clusters: A first-principles study

Abstract: In this paper, we have constructed the alloy configurations of Mg28-nAln by replacing atoms at various possible positions, starting from the stable structures of Mg28 and Al28 clusters. According to the symmetry of the cluster structure, the isomers of these initial structures have been screened with the congruence check, which would reduce computational hours and improve efficiency. Using the first-principles method, the structural evolution, mixing behavior and electronic properties of Mg28-nAln clusters are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…A negative value indicates a favorable mixing tendency and a greater stability. It can be defined as follows (Lu et al, 2017):…”
Section: View(atoms)mentioning
confidence: 99%
“…A negative value indicates a favorable mixing tendency and a greater stability. It can be defined as follows (Lu et al, 2017):…”
Section: View(atoms)mentioning
confidence: 99%
“…We have adopted CALYPSO method to investigate the Mg-Al binary alloy clusters, [90] as shown in 20 valence electrons and large energy gap, is identified to be magic cluster. [90] Moreover, another similar work, [91] focused on Mg 28−n Al n cluster, has reported five different stoichiometries of Mg-Al clusters, which present outstanding thermodynamic stabilities. As for RuGe n cluster, we have reported a systematic study of the relative stability and electronic properties of Ru-doped Ge clusters in the size range of 3 ≤ n ≤ 12.…”
Section: Other Functional Clustersmentioning
confidence: 99%
“…While Al atoms prefer to occupy the inner (endohedral) sites, the Mg atoms form the surfaces of the clusters. The neutral mixed Mg 24 Al 4 , Mg 21 Al 7 , Mg 14 Al 14 , Mg 26 Al 2 , and Mg 27 Al 1 and “magic” mononuclear Mg 10 and Mg 17 clusters were predicted to be the most stable species (see refs and for details).…”
Section: Introductionmentioning
confidence: 99%
“…To date, hydrides of the Mg m H n series ( m = 1–4 and n = 1–8), mixed magnesium–aluminum clusters Al n Mg m ( m ≤ 3, n + m ≤ 15), and their negative ions have been detected experimentally. Their DFT calculations demonstrated that the most stable species are the “magic” clusters Al 5 Mg 2 – , Al 11 Mg 2 – , Al 7 Mg 3 – , and Al 11 Mg 3 – . Systematic DFT studies performed for a wider family of mixed Mg 28– n Al n clusters ( n = 0–28), Mg 55‑ n Al n ( n = 0–55), and homonuclear Mg n isomers ( n = 2–56) ,, have demonstrated that the enthalpies of Mg/Al mixing are negative for all components. While Al atoms prefer to occupy the inner (endohedral) sites, the Mg atoms form the surfaces of the clusters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation